Exploring University Students’ Attitudes towards Primary Care: Evidence from a Cross-Sectional Study - Gianluca Voglino; Giuseppina Lo Moro; Maria Rosaria Gualano; Fabrizio Bert; Roberta Siliquini (The Scientific World Journal)
The general practitioner (GP) has a significant role in primary care, being more than a gatekeeper to health services access. In Italy, if a citizen moves for studies for at least 3 months, he/she can choose temporarily another GP in the new city (the so-called “Healthcare Domicile” (HD)). The aims were to estimate the university students’ knowledge about the HD, evaluate the frequency of the transition to another GP, and assess the university students’ attitudes towards the primary care services. In 2018, a cross-sectional pilot study was performed in study rooms among students attending the University of Turin Participation was voluntary, anonymous, and without compensation. A 25-item questionnaire collected information about the sociodemographic characteristics, health services use, health conditions and medications, HD knowledge, and HD use. The outcomes were having the GP far away, knowing HD, and not moving the GP even if aware of HD. Chi-square test, Mann–Whitney U-test, and logistic regression analyses were performed. The significance level was p≤0.05. Participants were 388 and those who knew HD were 45.36%. Among those who moved to Turin (44.85%), 77.67% knew HD but did not move the GP anyway. The 72.68% used medications without prescription (the most taken: nonsteroidal anti-inflammatory drugs and antibiotics). Age, nationality, and degree course type could be predictors for outcomes considered. HD knowledge was associated with a different use of healthcare resources. The data of the present paper suggest that further studies are required to better understand the framework connected with the university students’ access to primary healthcare. Our results highlighted the need to implement campaigns targeted to university students to spread information about the HD and a more appropriate use of the healthcare services and medications.